Large chemokine binding spectrum of human and mouse atypical chemokine receptor GPR182 (ACKR5) - Bonnavion, Remy; Liu, Shangmin; Kawase, Haruya; Roquid, Kenneth Anthony; Offermanns, Stefan (Frontiers in Pharmacology, 2023)
Atypical chemokine receptors (ACKRs) play pivotal roles in immune regulation by binding chemokines and regulating their spatial distribution without inducing G-protein activation.Recently, GPR182, provisionally named ACKR5, was identified as a novel ACKR expressed in microvascular and lymphatic endothelial cells, with functions in hematopoietic stem cell homeostasis. Here, we comprehensively investigated the chemokine binding profile of human and mouse GPR182. Competitive binding assays using flow cytometry revealed that besides CXCL10, CXCL12 and CXCL13, also human and mouse CXCL11, CXCL14 and CCL25, as well as human CCL1, CCL11, CCL19, CCL26, XCL1 and mouse CCL22, CCL24, CCL27 and CCL28 bind with an affinity of less than 100 nM to GPR182.In line with the binding affinity observed in vitro, elevated serum levels of CCL22, CCL24, CCL25, and CCL27 were observed in GPR182-deficient mice, underscoring the role of GPR182 in chemokine scavenging. These data show a broader chemokine binding repertoire of GPR182 than previously reported and they will be important for future work exploring the physiological and pathophysiological roles of GPR182, which we propose to be renamed atypical chemokine receptor 5 (ACKR5).